2011
DOI: 10.1111/j.1447-0756.2011.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal age on the incidence of obstetrical complications in Japan

Abstract: The effect of maternal age differs for each obstetrical complication, and thus, it is important to understand these differences for management of individual pregnant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 28 publications
7
28
2
Order By: Relevance
“…The odds decrease as the age of woman increases. The dose-response effect that age has on the odds for infection of chorioamnionitis and endometritis during labor and delivery (Cochran-Armitage trend tests p<.001) supports past studies 11,3739 and is of high clinical relevance. Bacteria from intrauterine infections during pregnancy can harm the fetus through systemic inflammation (a fetal inflammatory response syndrome) 40,41 and cause damage to multiple organs.…”
Section: Commentsupporting
confidence: 79%
“…The odds decrease as the age of woman increases. The dose-response effect that age has on the odds for infection of chorioamnionitis and endometritis during labor and delivery (Cochran-Armitage trend tests p<.001) supports past studies 11,3739 and is of high clinical relevance. Bacteria from intrauterine infections during pregnancy can harm the fetus through systemic inflammation (a fetal inflammatory response syndrome) 40,41 and cause damage to multiple organs.…”
Section: Commentsupporting
confidence: 79%
“…The main concern is a disparity in prevalence of coexisting diseases. The rates of chronic diseases were: thyroid disease, 12/547 (2.2%); chronic hypertension, 10/547 (1.8%); diabetes, 8/547 (1.5%); and renal disease, 4/547 (0.7%) in study participants, while those rates in the Japanese pregnant population are reported as: thyroid disease, 1.5%; chronic hypertension, 0.6%; diabetes, 2.1%; and renal disease, 1.1% . Although it appears that these small differences did not impact our main findings, caution should be exercised in generalizing our results.…”
Section: Discussionmentioning
confidence: 62%
“…This nationwide registry was established in 1974. Detailed descriptions of the database have been published previously (20). Briefly, the attending physicians at 125 tertiary centers of the Perinatal Research Network in Japan collected yearly data for each pregnant woman in an offline clinical database with a common format.…”
Section: Methodsmentioning
confidence: 99%